2023
DOI: 10.3390/bs13070561
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deviant Workplace Behavior on Job Performance: The Mediating Role of Organizational Shame and Moderating Role of Perceived Organizational Support

Abstract: It is not uncommon for employees to engage in deviant workplace behavior. Several studies have been conducted on its antecedent variables and negative effects on the organization and its members. However, the effects on employees’ emotions and behavior have been ignored. According to the affective events theory and framework of organizational shame, this study examined how deviant workplace behavior affects employee performance, explored how organizational shame mediates, and investigated the role of perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
1
1
Order By: Relevance
“…Moreover, a study by Angulo et al (2023), revealed that favorable organizational policies impact retention. Contrary to preceding discussions, research on the impact of deviant workplace behavior on job performance by Tian & Guo (2023) indicated that perceived organizational support mitigates the negative effects of disruptive workplace behavior on job performance. Similarly, demonstrated that social support in organizations reduces work stress, subsequently leading to increased job performance.…”
Section: Positive Workplace Environment and Relationshipscontrasting
confidence: 78%
See 1 more Smart Citation
“…Moreover, a study by Angulo et al (2023), revealed that favorable organizational policies impact retention. Contrary to preceding discussions, research on the impact of deviant workplace behavior on job performance by Tian & Guo (2023) indicated that perceived organizational support mitigates the negative effects of disruptive workplace behavior on job performance. Similarly, demonstrated that social support in organizations reduces work stress, subsequently leading to increased job performance.…”
Section: Positive Workplace Environment and Relationshipscontrasting
confidence: 78%
“…Expanding on this, research on job environments and job performance demonstrated the positive impact of the work environment on employees' job performance (Yusnita, 2023). Additionally, a study on deviant workplace behavior and job performance underscored the role of organizational support in enhancing job performance (Tian & Guo, 2023). Dealing with irate customers emerges as one of the most challenging situations for customer service and technical support call center agents.…”
Section: Customer Service and Technical Support Call Agents' General ...mentioning
confidence: 99%